1987
DOI: 10.1007/bf02796669
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of selenium against mercury toxicity as studied in the rat liver and kidney by nuclear analytical techniques

Abstract: Mercuric chloride and sodium selenite were separately administered to male rats in the drinking water or in a combination (2.5 mmol Hg/L and 0.1 mmol Se/L). The mercuric chloride group showed histopathological lesions, as evidenced by cell necrosis in the liver and tubular necrosis in the kidney. The sodium selenite group showed some depression in growth, but pathological changes were found neither in the liver nor in the kidney. Simultaneous administration of both compounds produced a protective effect on wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…(U-NAG = N-acetyl-β-D-glucosaminidase in urine, U-Albumin = urinary excretion of albumin, U-ALP = alkaline phosphatase in urine, S-creatinine = serum creatinine, U-Hg = mercury concentration in urine) Examination The negative associations that were found between U-NAG and the markers of selenium status suggest that selenium has an inhibitory effect on the excretion of U-NAG. Selenium has protective properties against the untoward effects of inorganic mercury exposure among animals (21,22), but little is known for humans. In our previous study, we found that selenium modified the effect of exposure to mercury vapor on the excretion of U-NAG (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(U-NAG = N-acetyl-β-D-glucosaminidase in urine, U-Albumin = urinary excretion of albumin, U-ALP = alkaline phosphatase in urine, S-creatinine = serum creatinine, U-Hg = mercury concentration in urine) Examination The negative associations that were found between U-NAG and the markers of selenium status suggest that selenium has an inhibitory effect on the excretion of U-NAG. Selenium has protective properties against the untoward effects of inorganic mercury exposure among animals (21,22), but little is known for humans. In our previous study, we found that selenium modified the effect of exposure to mercury vapor on the excretion of U-NAG (10).…”
Section: Discussionmentioning
confidence: 99%
“…Selenium may reduce the kidney toxicity of inorganic mercury in animals (21), in particular in the proximal tubule cells (22). Selenium may also protect the proximal tubule cells in patients receiving cis-platinum (23).…”
mentioning
confidence: 99%
“…Mercury in fish may not be as toxic as first thought because of the presence of selenium, which is clearly protective of the toxic effects of mercury (Lindh and Johansson 1987;Ralston 2008). For example, Mozaffarian (2009) reported that lower levels of nonfatal heart attacks are associated with higher levels of selenium.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, the knowledge of trace elements profile in hair matrices from children living in different parts of the world is primary in epidemiological studies using this matrix, since specific environment and ethnic conditions may modify the background levels. It is also important to determine the interaction between toxic and essential elements in hair, mostly because of the lack of such studies and the inconsistency of the results [9,10].…”
Section: Introductionmentioning
confidence: 99%